Artificial Intelligence (AI): An Opportunity and Challenge for Achieving Success in Islamic Education in the Era of Digital Transformation - Rifah, Rifah; Jailani, Mohammad; Huda, Miftachul (Universitas Muhammadiyah Surakarta, 2024)
Artificial Intelligence (AI) has become an integral part of digital literacy systems and plays a vital role in the development of intelligence. In the educational sector, AI represents a significant innovation that can greatly enhance the quality of learning and educational management. This technology offers numerous benefits, supporting educational stability and improving the teaching and learning processes. However, it is crucial to acknowledge that AI can also lead to adverse effects if misused. Therefore, ensuring the responsible use of AI in education is essential, adhering to applicable ethical standards. Educational institutions, particularly those with Islamic values, must continually innovate in response to technological advancements. At the same time, they should equip their students with strong religious values to mitigate potential harm that may arise from these technological developments. By fostering a balanced approach, educational institutions can leverage AI’s potential while safeguarding their students' moral and ethical foundations.